ANALISIS MODEL PROPAGASI OKUMURAHATA UNTUK LINK TERRESTIAL ANTENAPEMANCAR TV TOWER TURYAPADA - Agnes Pramudiawati, Araselly; Ratna Warsitasari, Ni Luh Nyoman; Surya Juliantara, Putu; Oka Widyantara, I Made; Pramaita, Nyoman; Djuni Hartawan, IGAK. Diafari (Jurnal SPEKTRUM, 2024)
This research analyzes the performance of the Okumura-Hata propagation model in designing terrestrial link antennas for digital television transmitters at Tower Turyapada, Pegayaman Village, Buleleng. The findings are important for optimizing signal quality in regions with geographical challenges, such as mountains and valleys, which obstruct signal propagation. The primary focus of the study is to measure and compare signal field strength at four test points in North Bali using simulations to predict the performance of the propagation model under different topographical conditions. The simulation results are then compared with theoretical calculations to assess the model's accuracy and evaluate their alignment with established reference values. The results show that the Okumura-Hata model is not suitable and does not fully reflect the complex topography of Buleleng, as the simulation results were lower than the reference values. The study recommends using an alternative propagation model more suited to local geographical conditions, along with more detailed field measurements to ensure optimal signal quality throughout the coverage area.